Are climate change perceptions related with plastic policy support? Effects of climate change skepticism, guilt, and efficacy on the acceptance of the plastic tax - Miri Kim; Seoyong Kim; Sehyeok Jeon (PLoS ONE, 2025)
Achieving a circular economy requires solutions to plastic pollution problems. Plastic waste poses significant threats to both human and biological systems globally. Plastics are closely related to climate change because their production is based on fossil fuels. Plastic taxation is one approach to reducing plastic use. This study aimed to analyze how the climate change perception is related to the preference for plastic tax. A model was developed to examine the impacts of 11 variables in value, risk perception, and planned behavior acting as predictors on the support for plastic tax as the predicted variable. In particular, we focused on both direct and indirect association of the three variables in planned behavior, that is, climate skepticism, guilt, and efficacy about climate change crisis , on support for the plastic tax. The results showed that among value variables, environmentalism, altruism, and egalitarianism had a significantly positive relationship with the willingness to pay the plastic tax and materialism had a significant negative relationship. Regarding risk perception, perceived risk, knowledge, and trust had a significantly positive association with the willingness to pay the tax. Regarding planned behavior, skepticism, guilt, and efficacy had a significant association with willingness-to-pay the plastic tax, with climate change skepticism having a negative effect and guilt and efficacy having positive relationship. Regarding the moderation effect, skepticism had an interaction effect on materialism and emotion; guilt is associated with the impact of environmentalism, altruism, egalitarianism, perceived risk on the support for plastic tax; and efficacy is associated with the association of altruism and perceived risk with preference for plastic tax. These results suggest that climate change risk perception is associated with plastic reduction behaviors.